2017
DOI: 10.4172/clinical-skills.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Neck Stabilization Exercise on Neck Repositioning Accuracy in Chronic Neck Pain Patients

Abstract: Background: Forward head posture is a musculoskeletal abnormality where the head is positioned anterior to the Line of Gravity causing neck pain, headache, temporo-mandibular disorders, myofacial pain syndrome and abnormal scapular movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It was reported that PIR and RI partially explain the benefits of MET (11), which are relatively pain-free joint and soft tissue motion after mild isometric contractions (12). The NSE is a form of a rehabilitation program that was developed for the purpose of relieving pain, improving function, preventing further injury (13) as well as improving the innate mechanisms by which the cervical spine keep up a stable and injury-free state (14).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that PIR and RI partially explain the benefits of MET (11), which are relatively pain-free joint and soft tissue motion after mild isometric contractions (12). The NSE is a form of a rehabilitation program that was developed for the purpose of relieving pain, improving function, preventing further injury (13) as well as improving the innate mechanisms by which the cervical spine keep up a stable and injury-free state (14).…”
Section: Introductionmentioning
confidence: 99%